CHARACTERIZATION OF CRUDE CELLULASE OF SEAGRASS ENDOPHYTIC FUNGUS - Yulia Oktavia; Aulia Andhikawati; Tati Nurhayati; Kustiariyah Tarman (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2014)
In this study, cellulase was produced by endophytic fungus isolated from seagrass. Substrate used for incubating the fungus was the waste of agar industry. The objectives of this study were to optimize cellulase production and to characterize the highest activity of fungal crude cellulase. In our previous study, the EN isolate (isolated from Enhalus sp.) showed the highest cellulolytic index. Therefore, in this research we focused on cellulase activity of the isolate. Cellulase activity was determined based on endoglucanase activity, total cellulase activity, and β-glucosidase activity. The highest activity was then used to determine cellulase activity in enzyme characterization. The fungus was cultured in different concentration of agar extraction algal wastes. The fungal culture was incubated for 3-21 days with 120 rpm orbital shaker. The results showed that endoglucanase activity was 0.019-0.031 U/mL, total cellulase activity was 0.007-0.013 U/mL, and β-glucosidase activity was 0.00012-0.00361 U/mL. The highest endoglucanase and total cellulase activity were obtained from the fungal culture after 9 days incubation, β-glucosidase was obtained from the fungal culture after 15 days incubation with 1.5% of algal waste as substrate. The optimum pH and temperature were determined as 4 and 60 oC, maximum reaction rate (Vmax) and Michaelis-Menten constant (Km) for endoglucanase activity was determined as 0.044 U/mL and 0.103% respectively. Keywords: algal waste, cellulase, endophytes, enzymes, seagrass